Proses Pemekaran Wilayah Selatan Kabupaten Tangerang Menjadi Kota Tangerang Selatan (2000-2008) - Fikri, Muhammad; Hadi Wibowo, Tubagus Umar Syarif; Nurhasanah, Ana (Universitas Syiah Kuala, 2025)
The objectives of this research are: (1) Describe the background to the emergence of the southern region of Tangerang Regency to become a new autonomous region, (2) Analyze the process of regional expansion of South Tangerang City (2000-2008). The research method used is the historical research method which consists of heuristics, criticism, interpretation and historiography. The theory in this study uses the theory of regional expansion, the theory of decentralization and regional autonomy, and the theory of the city. This theory is used as an analysis of the research process of regional expansion, especially the southern region which became South Tangerang City in 2000-2008. The results of this study indicate that the background of this expansion stems from public concern over the process driven by rapid growth in the South, which has given rise to the need for better governance, especially related to infrastructure and public services that are felt to be less effective and efficient. This study highlights the role of local communities in it to fight to separate their regions with community organizations such as the Cipasera City Autonomous Region Formation Committee (KPPDO-KC), Bakor Cipasera, Formats, and the Ciputat Communication Forum (FKMC). Through a historical approach and analysis of the legislative framework, this study attempts to reconstruct the journey of decentralization which finally culminated in the formation of South Tangerang City based on Law Number 51 of 2008.Keywords: Process, Regional Expansion, South Tangerang City, 2000-2008